Software Defect Prevention through Orthogonal Defect Classification (ODC) - Kumaresh, Sakthi; Baskaran, R (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
â€œQuality is never an accident; it is always the result of intelligent effortâ€ [10]. In the process of making quality software product, it is necessary to have effective defect prevention process, which will minimize the risk of making defects /errors in software deliverables. An ideal approach would involve effective software development process with an integrated defect prevention process. This paper presents a Defect Prevention Model in which Defect Prevention Process(DPP) is integrated into software development life cycle to reduce the defects at early stages itself, thereby reducing the defect arrival rate as the project progresses to the subsequent stages. Orthogonal Defect Classification (ODC) scheme involving defect trigger, defect type etc. are discussed in this work to illustrate how ODC can be used in the defect prevention process. ODC can be used to measure development progress with respect to product quality and identify process problems, which will help to come out with â€œBest Practicesâ€ to be followed to eradicate the defects in the subsequent projects.